Positive psychology pioneers: Mihaly Csiksentmihalyi's power and potential to influence mental health nursing. (2nd May 2022) - Macfarlane, Jan
Abstract : This article is the second in a series that celebrates the work of positive psychologists and how their work has the power and potential to influence mental health nursing practice. Focusing on Mihaly Csikszentmihalyi (1934–2021) and his work on flow will help to bring interest and understanding to this exciting and developing area of mental health nursing practice. The practical activities provided in the article will help the reader increase their own awareness of flow to develop its use and transferability within their own life.